Fertility preservation in uterine cervix cancer initial stages - Rosazza, Percy (2014)
The incidence of cervical cancer has increased in young women in whom it is important to reserve fertility. Two cases of patients with early cervical cancer stages IA2 e IB1 and no pelvic lymph nodes metastasis are presented, and experience with abdominal radical trachelectomy in order to preserve fertility is analized.